Tentacular Aesthetics: Artistic Encounters beyond the Human (Revista Estado da Arte, 2025)
This article discusses how artworks can raise empathy for octopuses by means of documenting, storytelling, and strategic anthropomorphism. Formerly, octopuses have mostly been depicted for their ornamental, decorative, and symbolic value. But in the light of a new sensibility for more-than-human lives in the Anthropocene (or rather Chthulucene), a new generation of artists stresses the intelligence and sentience of these invertebrates who have long been regarded as the absolute other. They take interest in octopus agency, octopus creativity, and octopus ethics by trying to give access to their alternate worldviews in imaginary and experimental ways.